Neurologic disorders in 4858 survivors of central nervous system tumors in childhood—an Adult Life after Childhood Cancer in Scandinavia (ALiCCS) study. Issue 1 (30th May 2018) - Kenborg, Line; Winther, Jeanette Falck; Linnet, Karen Markussen; Krøyer, Anja; Albieri, Vanna; Holmqvist, Anna Sällfors; Tryggvadottir, Laufey; Madanat-Harjuoja, Laura Maria; Stovall, Marilyn; Hasle, Henrik; Olsen, Jørgen H; ,
Abstract: Background: A comprehensive overview of neurologic complications among survivors of central nervous system (CNS) tumors in childhood is lacking. We aimed to investigate the risk for these disorders in a large, population-based study with outcome measures from nationwide hospital registries. Methods: We identified 4858 five-year survivors with diagnoses of CNS tumor in childhood in Denmark, Iceland, Finland, and Sweden in 1943–2007, and 166658 matched population comparison subjects. Inpatient discharge diagnoses of neurologic disorders were used to calculate relative risks (RRs) and absolute excess risks (AERs). Results: A neurologic disorder was verified in 1309 survivors, while 92.4 were expected, yielding an overall RR of 14.2 (95% confidence interval [CI]: 13.3–15.1) and an AER of 20 hospitalizations per 1000 persons per year. The risks remained increased more than 20 years after diagnosis (RR: 6.3, 95% CI: 5.6–7.2; AER: 11, 9–12). The most frequent diagnoses were epilepsy (affecting 14.1% of all survivors) followed by hydrocephalus (9.5%) and paralytic syndromes (4.2%), with RRs of 28.7 (95% CI: 26.0–31.6), 243 (95% CI: 190–311), and 40.3 (95% CI: 33.1–49.2), respectively. Of these outcomes, 30%–40% were diagnosed prior to or synchronously with the CNS tumor. The survivors had highly increased RRs for infectious diseases of the CNS, disorders of cranial nerves, and degenerative diseases of the nervous system. Conclusions: Survivors of childhood CNS tumors are at markedly increased risk for neurologic disorders throughout their lives. Health care professionals must be aware of survivors who might benefit from preventive interventions and intensive follow-up.